Epidemiology and Genetics of Venous Thromboembolism and Chronic Venous Disease. Issue 12 (11th June 2021) - Baylis, Richard A.; Smith, Nicholas L.; Klarin, Derek; Fukaya, Eri
Abstract : Venous disease is a term that broadly covers both venous thromboembolic disease and chronic venous disease. The basic pathophysiology of venous thromboembolism and chronic venous disease differ as venous thromboembolism results from an imbalance of hemostasis and thrombosis while chronic venous disease occurs in the setting of tissue damage because of prolonged venous hypertension. Both diseases are common and account for significant mortality and morbidity, respectively, and collectively make up a large health care burden. Despite both diseases having well-characterized environmental components, it has been known for decades that family history is an important risk factor, implicating a genetic element to a patient's risk. Our understanding of the pathogenesis of these diseases has greatly benefited from an expansion of population genetic studies from pioneering familial studies to large genome-wide association studies; we now have multiple risk loci for each venous disease. In this review, we will highlight the current state of knowledge on the epidemiology and genetics of venous thromboembolism and chronic venous disease and directions for future research.